Information, uncertainty, and subjective entitlements in bargaining - Emin Karagözoğlu; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2010)
More often than not production processes are the joint endeavor of people having different abilities and productivities. Such production processes and the associated surplus production are often not fully transparent in the sense that the relative contributions of involved agents are blurred; either by lack of information about the actual performance of collaborators or because of random noise in the production process or both. These variables likely influence the surplus sharing negotiations following the production. By means of a laboratory experiment, we systematically investigate their role for the whole bargaining process from opening offers to (dis)agreements and find that uncertainties in surplus production and (even) a very coarse performance information lead to bargaining asymmetries. In addition, we find that bargainers' subjective entitlements are also influenced by performance information and the randomness inherent in the production process. These differences in subjective entitlements together with the differences in entitlements between better and worse performers influence the whole bargaining process and significantly contribute to the differences in bargaining outcomes.
Keywords: C79; C92; D01; D29; D63; D89; M59; 330; bargaining; performance information; randomness in production process; entitlements; experiments; Verhandlungstheorie; Personalbeurteilung; Asymmetrische Information; Sportökonomik; Risiko; Test